Progression from Type 2 Macular Neovascularization to Fibrovascular Pigment Epithelial Detachment - LE, Hoang Mai (Vision (Basel), 2021)
The aim of this study was to report unusual progression of type 2 macular neovascularization (MNV) associated with age-related macular degeneration (AMD), high myopia or angioid streaks. Retrospective multicentric observational case series data were used. Eyes that progressed from type 2 MNV secondary to AMD, high myopia or angioid streaks to fibrovascular pigment epithelial detachment (PED) were included. A total of 29 treatment-naive eyes from 29 patients with type 2 MNV secondary to AMD (n = 14), high myopia (n = 10) or angioid streaks (n = 5) that progressed to a fibrovascular PED on Spectral Domain-Optical Coherence Tomography were used. This progression occurred within 3 months after anti-VEGF therapy initiation. Logarithm of minimum angle of resolution (LogMAR) visual acuity improved significantly after anti-VEGF therapy, from 0.55 (SD ± 0.30) (20/63–20/80) at baseline to 0.30 (20/40) at 3 months, and 0.33 (20/40) at the final follow-up (mean follow up: 3.68 years). Mean number of intravitreal injections per year for patients with a total follow-up ≥ 12 months (n = 24) was 4.3 ± 2.1 per year. Progression from type 2 MNV to a fibrovascular PED may occur in patients suffering from AMD, high myopia or angioid streaks. This progression appears early after initiation of anti-VEGF therapy and is associated with a favorable visual and anatomical outcome, at least on a short follow up basis.